Investment Analysis in the Indonesian Capital Market - Meigia Nidya Sari; An Suci Azzahra (Universitas 17 Agustus 1945 Semarang, 2023)
This research explains how investment in the capital market has developed, this article tries to outline several risks that have the potential to occur in investing in the capital market. Keywords; Risk, Investment, and Capital Markets Abstract The capital market is a place where companies seek funds to finance their business activities. Apart from that, the capital market also collects public funds directly by investing funds into healthy and well-managed companies. The main function of the capital market is as a means of capital formation and accumulation of funds for financing a company/issuer. The presence of capital market institutions in Indonesia adds to the list of alternatives for people who have excess funds and are interested in investing in their funds. This article tries to explain how investment in the capital market is developing, besides this, this article tries to explain some of the risks that have the potential to occur in investing in the capital market.